A SUSTAINABLE ARCHITECTURAL CONCEPT APPROACH TO MOSQUE DESIGN IN MEDAN - Syahputra, Dany; Iskandar, Benny; Nuraini, Cut (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
A mosque is a building of worship that is widely spread in Indonesia, because many of these buildings are found because the majority of the population in Indonesia is Muslim. A mosque is a place that not only functions for worship but also contains beauty, holiness and a sense of comfort for future users. methods or approaches, including data collection methods, literature, site location surveys, discussion and data analysis and concept formulation design. This data is then grouped again to create a room. The space is in the form of a zoning drawing of the shape of a mosque, as well as other supporting facilities. Ideas for designing a mosque area that can accommodate the needs of its future users by providing a sustainable architectural approach. The design concept for this mosque carries the concept of sustainable architecture which can maximize its function other than for worship. As for sustainable architecture, several literatures reveal that the application of a building context with the concept of sustainable architecture also gives a comfortable impression and is aimed at environmentally friendly development, which utilizes natural potential as much as possible. Sustainable architecture is an environmentally friendly building, which is designed and built using sustainable building technology, sustainable energy systems, sustainable building materials and sustainable building materials that do not burden future generations with environmental and financial debt.